Aplasia cutis congenita and methimazole. A case report and literature review. - Tasin, L.; Belli, S.; Chiodini, E. (European Journal of Pediatric Dermatology, 2005)
Aplasia cutis congenita -ACC- is a rare group of disorders characterized by focal absence of skin at birth. the lack of skin involves the scalp in most cases, but also trunk and limbs can be affected. Frieden classified ACC into nine types according to the associated anomalies, but a unifying theory has not been identified to explain the etiology of this disease. We present the case of a newborn who showed a lack of skin on the scalp at birth. His mother was affected by hyperthyroidism treated with methimazole during pregnancy. we noted also a distinctive type of hair growth defect, usually not mentioned as an associated anomaly. We recommend propylthiouracil for treating thyrotoxicosis in pregnant women until further data on the safety of methimazole are available.